Medlar (Mespilus germanica L.) fruit morphology depending on fruit size (Journal of Forestry, 2025)
The present study aims to investigate the effects of fruit size of medlar (Mespilus germanica L.) on fruit and seed morphology. Medlar fruits were harvested from the crowns of ten trees near Đulovac, Croatia, in autumn 2022 and 2023 at commercial maturity. Before morphological analysis, the fruits were divided into three groups according to their weight: small (< 14g), medium-sized (14 – 17g) and large (> 17g). Fruit size, year and the interaction between the fruit size and year had a significant influence (P < 0.01) on fruit weight, fruit length, fruit width, geometric mean diameter, sphericity and fruit shape index. Fruit length and width showed a significant correlation with fruit weight in almost all cases, with the only exception of the medium-sized fruit in 2022 for fruit length. Fruit sphericity was positively correlated with fruit width and negatively correlated with fruit length and fruit shape index. The number of filled seeds per fruit correlated only slightly or not at all with fruit weight, fruit length, fruit width, fruit shape index and the geometric mean diameter of the fruit. The results of the discriminant analysis show that large fruits harvested in 2022 and 2023 can be clearly separated from other fruit categories, which can be attributed to effect of crop load on fruit morphology. It can be concluded that there is a high variability of medlar fruits even at a single location and thus that they have high breeding potential. Therefore, future studies analysing the entire area of the Republic of Croatia are needed.